The Magi who they were, how they've been remembered, and why they still fascinate - Vanden Eykel, Eric M. (Minneapolis, MN Fortress Press, 2022)
Ancient historian and scholar Eric Vanden Eykel helps readers better understand both the Magi and the ancient and modern interpreters who have tried to study them. He shows how, from a mere twelve verses in the Gospel of Matthew, a varied and vast literary and artistic tradition was born. The Magi examines the birth of the Magi story; its enrichments, embellishments, and expansions in apocryphal writing and early Christian preaching; its artistic expressions in catacombs, icons, and paintings; and its modern legacy in novels, poetry, and music. Throughout, the book explores the fascination the Magi story elicits in both ancient and modern readers and what the legacy of the Magi story tells us about its storytellers--and ourselves
Authors, readers, and meanings -- Magicians, wise guys, and translators -- Frescoes, funny hats, and faraway places -- Sages, a star, and the search for the true king -- Mushrooms, armies, and secrets as old as the world -- Horoscopes, hymns, and shifting ground -- Buddhists, watches, and endings.
Includes bibliographical references (pages 205-214) and index
Keywords: Jesus Christ -- Nativity; Jesus Christ; Magi; Magi; Nativity of Jesus Christ; Religious materials; Religious materials